The Effectiveness of the ‘Extended Sick Neonatal Score in Predicting Mortality in a ResourceConstrained Neonatal Care Uni - Rehman, Romisa; Razzaq, Asma; Ahmad, Asad Maqbool; Rehman, Zarlish; Rehman, Roshaan; Ateeq, Saad (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To determine the diagnostic accuracy of the extended sick neonatal score (ESNS) in neonates admitted in a resource-limited neonatal intensive care unit (NICU) at Peshawar. Study Design: Cross-sectional analytical study Place and Duration of Study: Neonatal Intensive Care Unit, CMH Peshawar Pakistan, from Mar to May 2020. Methodology: Primary data was collected from 60 neonates admitted to NICU after taking consent from the parents. The receiver operating characteristic curve (ROC) was plotted to determine the clinical score (ESNS) cut-off value in predicting mortality. Result: The sensitivity and specificity of the Extended sick neonatal score to predict mortality among neonates was 93.3% and 97%, respectively, for a cut-off of 12.5. The area under the ROC curve was 0.990 (95% CI: 0.971–1.000). This was statistically significant with a p-value of <0.001 Conclusion: Extended Sick Neonatal score is an important tool that helps predict the risk of mortality of a neonate without the help of any invasive diagnostic procedure, thus enhancing the prioritization of health care to the most deserving neonates.